Perinatal outcome and need of care for term asphyxiated newborns without moderate or severe hypoxic‐ischemic encephalopathy. (3rd December 2021) - Bower, Alexandra; Lorain, Perrine; Kayem, Gilles; Dommergues, Marc; Foix‐L'Hélias, Laurence; Guellec, Isabelle
Abstract: Aim: Birth asphyxia can lead to organ dysfunction, varying from isolated biological acidosis to hypoxic‐ischemic encephalopathy (HIE). Pathophysiology of moderate or severe HIE is now well known and guidelines exist regarding the care required in this situation. However, for newborns without moderate or severe HIE, no consensus is available. Our objective was to describe the immediate neonatal consequences and need for care of asphyxiated newborns without moderate or severe HIE. Methods: Multicentre retrospective study from January 2015 to December 2017 in two academic centres, including neonates ≥37 gestational weeks with pathological foetal acidemia (umbilical arterial pH<7.00 and/or lactate≥10 mmol/L). Results: Among 18 550 births, 161 (0.9%) had pathological foetal acidemia. 142 (88.0%) were not diagnosed with moderate or severe HIE. Among them, 82 (58.0%) were hospitalised. 13 (9.0%) had respiratory failure and required nutritional support. 100 (70.0%) underwent blood sampling, which showed at least one biological anomaly in 66 (66.0%) of cases. Conclusion: Newborns born with pathological foetal acidemia without the occurrence of moderate or severe HIE had metabolic disorders and could need organ support. A prospective study describing this vulnerable population would help to establish consensus guidelines for the management of this population.